Revision of the genus Centistes (Hymenoptera: Braconidae: Euphorinae: Centistini) of Costa Rica - Aguirre, Helmuth; de Almeida, Luis Felipe Ventura; Shaw, Scott Richard (Zootaxa, 2017)
This paper provides the first taxonomic revision for the euphorine genus Centistes from a Neotropical country. Twenty-three new species are described: C. achterbergi sp. n., C. acuticaudatus sp. n., C. auricephalus sp. n., C. auristigma sp. n., C. bicaudatus sp. n., C. cabecares sp. n., C. cartagoensis sp. n., C. chorotegus sp. n., C. compactus sp. n., C. curvicaudatus sp. n., C. gauldi sp. n., C. hansoni sp. n., C. hirsutus sp. n., C. janzeni sp. n., C. laticaudatus sp. n., C. longicaudatus sp. n., C. marshi sp. n., C. muertensis sp. n., C. ornamentum sp. n., C. pilosus sp. n., C. puntarenensis sp. n., C. sergeyi sp. n., C. zurquiensis sp. n. A taxonomic key, including the two previously described species, C. epicaeri Muesebeck and C. gasseni Shaw, is presented. As a whole, the Centistes exhibit their highest diversity in the premontane cloud forests.